KESADARAN DAN PARTISIPSI PEDAGANG PASAR RAYA DI KOTA PADANG TERHADAP PROTOKOL KESEHATAN DI ERA NEW NORMAL - An Nisa' May Fitri; Afdhal Afdhal (JURUSAN GEOGRAFI FIS UNP, 2021)
This study aims to analyze: 1) Awareness of Pasar Raya Traders in Padang City in the New Normal Era 2) Participation of Pasar Raya Traders in Padang City in the New Normal Era. This type of research is descriptive with a quantitative approach. The population of this research is the main market traders in the city of Padang. The population of this research is 38 traders. Data collection using questionnaires and documentation. The data analysis technique used in this research is descriptive quantitative. The results of this study found that 1) The awareness of the Padang market traders towards health protocols was moderate with a percentage of 63.87% because some traders no longer fully believed in the existence of the corona virus disease (Covid-19). 2) Participation of Padang market traders towards health protocols is classified as moderate with a percentage of 49.33% and this is classified as lower when compared to the awareness percentage of the Padang Raya market traders because traders no longer care about the existence of health protocol policies from the government and other factors due to difficulties in implementing new normal habits during a pandemic.Keywords: teacher performance, reaserch and publication, self-development, innovative work